Study on Co-Crystallization of LCZ696 Using In Situ ATR-FTIR and Imaging - Xiao Juan Liu (Crystals, 2020)
In situ ATR-FTIR spectroscopy and imaging and image analysis were applied to the study of the multicomponent co-crystallization process involving S-valsartan and sacubitril in which LCZ696 crystals were formed. LCZ696 is a combination drug for use in heart failure that was approved by the FDA in 2015 following development by Novartis Pharmaceuticals. Though much work was reported on LCZ696 about its pharmacokinetic and pharmacodynamic effects in the evaluation and clinical testing, less attention was paid to study on the co-crystallization process. LCZ696 crystals have shown difficulties in filtration mainly due to the small particle size. In this work, LCZ696 crystals were prepared successfully by S-valsartan and sacubitril, and characterized by SEM, XRPD, TG-DSC and ATR-FTIR. ATR-FTIR and imaging and image analysis were used to monitoring solution concentration and investigating the co-crystallization mechanism. It revealed that the nucleation process was very slow compared with the transformation process, which is indication that the co-crystallization was controlled by nucleation. LCZ696 crystals are composed of very thin hexagonal plates, which seems indicating that LCZ696 crystals grow mainly in two size dimensions. Stirrer speed and crystal seeds were found to have noticeable effect on the induction time, transformation time and crystal size distribution. The Johnson-Mehl-Avrami equation was found to be able to describe the co-crystallization process.